Analysis of the Energy and Emission Performance of an Automatic Biomass Boiler in the Context of Efficient Heat Management - Adam Nocoń; Artur Jachimowski; Wacław Koniuch; Grzegorz Pełka; Wojciech Luboń; Paweł Kubarek; Marta Jach-Nocoń; Dominika Dawiec (Energies)
This paper presents the results of an examination of an automatic biomass boiler identifying its strengths and weaknesses and computing its seasonal energy and emission parameters. The boiler was found to meet the energy and emission requirements for distribution in Poland. The boiler is characterised by good heating efficiency and low dust and carbon monoxide emissions. The aim of this paper is to provide and analyse these parameters, and by doing so classify it in the context of its competitors. The average heating output is 26.86 kW and the thermal efficiency is 87.97%. Carbon monoxide emissions are very low (22.71 mg/m3). However, nitrogen oxide emissions (187.6 mg/m3) can be a problem. Filters made out of metalworking waste, i.e., machining shavings, significantly improve the boiler performance, contributing to an increased heat output and efficiency and reduced dust emissions. Compared with other solutions available in the market, the boiler compares favourably in terms of dust and carbon monoxide emissions and is also characterised by similar efficiency, especially with the filters in place. Regarding the context of thermal energy management, the appliance under investigation demonstrates not only favourable energy and emission parameters, but also the potential for the efficient use of thermal energy, which can bring additional economic and environmental benefits.